GAMBARAN TINGKAT DIGITAL HEALTH LITERACY PENDERITA DIABETES MELITUS DI PUSKESMAS BULELENG I PADA MASA PANDEMI COVID-19 - Dewi, I Gusti Ayu Putu Anggitha Puja Laskmi; Rahajeng, Indah Mei; Suarningsih, Ni Kadek Ayu; Widyanthari, Desak Made (Coping: Community of Publishing in Nursing, 2022)
The COVID-19 pandemic has been challenging for people with Diabetes Mellitus (DM) in accessing health services in Indonesia. The increase in the incidence of DM during the COVID-19 pandemic occurred in Buleleng Regency, especially the Community Health Center Buleleng I. The government recommends using information technology for DM self-management. The ability to access technology and health information in DM self-management can be projected from the level of digital health literacy. This study aims to describe the level of digital health literacy among DM patients at the Community Health Center Buleleng I during the COVID-19 pandemic. This was a descriptive study with a survey approach. Respondents as many as 67 people selected by consecutive sampling technique. Data was analysed using descriptive statistical analysis. The results show the level of digital health literacy low (50,7%). The characteristic of the respondents are the age range of 57-66 years (32,8%), male (31,3%), have been living with DM for 1-5 years (41,4%), and monthly income below average (47,8%).